Long-term course of untreated asymptomatic esophageal eosinophilia and minimally symptomatic eosinophilic esophagitis - Abe, Yasuhiko; Kikuchi, Ryosuke; Sasaki, Yu; Mizumoto, Naoko; Yagi, Makoto; Onozato, Yusuke; Watabe, Takahiro; Goto, Hiroki; Miura, Takahiro; Sato, Ryou; Ito, Minami; Tsuchiya, Hiroko; Ueno, Yoshiyuki (Endoscopy International Open, 2024)
Background and study aims The long-term course of untreated asymptomatic esophageal eosinophilia (aEE) and minimally symptomatic eosinophilic esophagitis (mEoE) are not well understood. This study aimed to clarify this course.Patients and methods A total of 36 patients with EE who were endoscopically followed up for more than 5 years, and who underwent more than one endoscopy evaluation after the first diagnosis, were investigated. These patients were divided into two groups according to the presence or absence of the continuous treatment: no treatment group (NT group, n=22) and proton pump inhibitor/potassium competitive acid blocker group (Tx group, n=14). Symptoms and endoscopic and histological findings were retrospectively reviewed according to endoscopic phenotypes. Endoscopic assessment was performed using the EoE endoscopic reference score (EREFS).Results The median follow-up period was 84.5 months in the Tx group and 92 months in the NT group. During the follow-up period, about half of the patients in the Tx-diffuse group persisted EREFS >3, while the remaining half had EREFS ≤2. The total EREFS in the NT-diffuse group remained almost unchanged (median: 2–4) without apparent exacerbation. In contrast, EREFS in the NT-localized group exhibited an unchanged or gradually decreasing trend, with statistical significance from the first diagnosis to 72 to 83 months after.Conclusions Untreated aEE and mEoE are not likely to worsen even without treatment at least for a median follow-up of 7 years. Instead, the localized type may spontaneously improve, implying a different pathogenesis in the presence of the diffuse type. Further studies should clarify the long-term prognosis.
Keywords: Endoscopy Upper GI Tract; Eosinophilic esophagitis; GI Pathology; Epidemiology